ECO-AI BASED ISLAMIC EDUCATION MANAGEMENT: MPI 5.0 INNOVATION BASED ON OUTCOME-BASED EDUCATION TO ACHIEVE SUSTAINABLE ACADEMIC EXCELLENCE - Ulfatul Ainiyah; Tatik Hidayati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The transformation of Society 5.0 presents a new dilemma for Islamic educational institutions, namely how to integrate artificial intelligence (AI) into academic governance without ignoring the principles of ecological sustainability and Islamic values. This article aims to formulate a conceptual model of Eco-AI Based Islamic Education Management as an innovation of the fifth generation of Islamic Education Management (MPI 5.0) based on the Outcome Based Education (OBE) paradigm to realize sustainable academic excellence. This study uses a library research method with a qualitative descriptive-analytical approach through a conceptual synthesis of Islamic education management, Green/Eco-AI, and OBE literature published between 2018 and 2026. The results of the study indicate that MPI 5.0 is a dialectical continuation of the digital transformation of madrasahs and Islamic boarding schools in the Society 5.0 era that places the values of shura and maqashid sharia as ethical controllers of AI utilization. The integration of OBE provides a framework for aligning graduate learning outcomes with sustainable quality indicators, while the Eco-AI principles encompass the dimensions of green in AI and green by AI, ensuring that the adoption of intelligent technologies does not increase the institution's carbon footprint. The proposed conceptual model consists of four interrelated pillars: Islamic ethical digital governance, an outcomes-oriented curriculum, energy-efficient AI infrastructure, and an environmentally friendly academic culture (eco-campus). This article contributes to the development of a new theoretical framework for managers of Islamic religious universities and Islamic boarding schools (pesantren) in designing adaptive, ethical, and sustainable digital transformation policies.